The Effectiveness of Using Muroja'ah Animation Media For Kids on the Ability to Memorize Al-Quran in Kindergarten: Efektivitas Penggunaan Media Animasi Muroja'ah For Kids Terhadap Kemampuan Menghafal Al-Quran di Taman Kanak - Megadewi Anjarsari; Anita Puji Astutik (Academia Open, 2022)
The use of this muroja'ah animation media is a way out to help students at ABA 1 Sukodono Kindergarten in memorizing the Qur'an. Against the background that to memorize the Qur'an, children still use the first method, namely reading the Qur'an and then memorizing it, but this method can usually be boring in memorizing the Qur'an, for the ability to memorize it will take a long time to increase if memorize it in a state of boredom and lack of enthusiasm. The problem formulation of this research is how easy it is to memorize the Qur'an so that when memorizing it does not get bored quickly and is more enthusiastic. The purpose of this study is to create an animation media to improve the ability to memorize the Qur'an. The research method used is an experimental quantitative method, namely research conducted to examine a problem from the phenomenon, as well as the relationship with the problem determined in the form of causality or functional . The data collection technique is to collect data in the form of student learning outcomes before and after using animation media. Data analysis is in the form of normality test, and homogeneity test. The results of this study indicate that the use of muroja'ah animation media is effective on memorization skills in Asyiyatul Bustanul Athfal 1 Sukodono Kindergarten. This is evidenced by an increase in the results of the pretest and posttest.